(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article is dedicated to the role and advantages in using information technology (IT) in the process of teaching foreign languages in higher and secondary education, as well approaches to its use. The article discusses the definition and place of IT in the context of education and teaching, new opportunities in methodology, as well as requirements from both teachers and learners in using IT-based educational approaches. It also provides an analysis of possible challenges in applying IT in learning languages.